Integrated Study of X-Ray Spectrum and Time Lags for HBL Mrk 421 within the Framework of the Multiple-zone Leptonic Model - Hu, Wen; Kang, Jia-Lai; Cai, Zhen-Yi; Wang, Jun-Xian; Su, Zhen-Bo; Xiao, Guang-Cheng (The Astrophysical journal, 2024)
We present the timing analysis of 10 archived XMM-Newton observations with an exposure of >40 ks of Markarian 421. Mrk 421 is the brightest high-frequency-peaked BL Lac object emitting in X-rays produced by electrons accelerated in the innermost regions of a relativistic jet pointing toward us. For each observation, we construct averaged X-ray spectra in 0.5–10 keV band, as well as 100 s binned light curves (LCs) in various subbands. During these observations, the source exhibited various intensity states differing by close to an order of magnitude in flux, with the fractional variability amplitude increasing with energy through the X-ray band. Bayesian power spectral density analysis reveals that the X-ray variability can be characterized by a colored noise, with an index ranging from ∼ −1.9 to −3.0. Moreover, both the standard cross-correlation function and cross-spectral methods indicate that the amount of time lags increases with the energy difference between two compared LCs. A time-dependent two-zone jet model is developed to extract physical information from the X-ray emission of Mrk 421. In the model, we assume that the jet emission mostly comprises a quasi-stationary component and a highly variable one. Our results show that the two-zone model can simultaneously provide a satisfactory description for both the X-ray spectra and time lags observed in different epochs, with the model parameters constrained in a fully acceptable interval. We suggest that shocks within the jets may be the primary energy dissipation process responsible for triggering the rapid variability, although magnetic reconnection cannot be excluded.